RECONCEPTUALISING EUCHARIST AS SUBSERVIENT RITUAL: A MISSIOLOGICAL RESPONSE TO PUBLIC VIOLENCE IN AFRICA - Kaunda, Chammah J. (Scriptura, 2015)
In this article, I argue that the church as Christ’s symbolic presence in the world is a Missiological expression of God loving non-violent involvement and witnessing presence in the world permeated with violence. Through two case studies that exemplify the relationship between public speech and public violence - the 1994 Rwandan genocide and the 2015 xenophobic attacks in South Africa - the article demonstrates the potential of liminality of Eucharistic encounter to inspire and empower African Christians prophetically to respond non-violently to the plague of public violence in many African countries.